HYDROGELS FROM WATER-SOLUBLE BORONATED POLY(ETHYLENE GLYCOL) (PEG)-LINKERS WITH POLY(VINYL ALCOHOL) - Dewi Hujaya, Sry
In the biomedical world, especially in the search for sophisticated advanced drug delivery and targeting systems (DDTS), boronic acid-containing hydrogels attract a unique attention due to its specific interaction with compounds that contain 1,2- and/or 1,3-diol moieties and its reversible complex (or crosslink) formation that provides such system with a self-healing property. Such hydrogels have been known to be responsive to the change in ionic condition, pH, temperature, and presence of diol-containing molecules such as glucose. However, the development of these boronic acid-containing hydrogels is usually hampered by the relatively weak crosslink at around physiological pH and water-solubility problems. We herein report the successful syntheses of a series of novel multiarm boronated poly(ethylene glycol) (PEG)-linkers via reductive amination of amine-functionalized multiarm PEGs with formyl phenylboronic acid. Linkers with various molecular architectures differing in both number and length of the arms were synthesized and studied for their effects on gelation properties with poly(vinyl alcohol) (PVA) through dynamic rheology measurements. With this novel linker system, hydrogels with high storage (or elastic) modulus up to 30 kPa were attainable in phosphate buffer saline (PBS buffer) pH 7.4. Crosslinking mechanism was confirmed to be due to the specific interaction between phenylboronic acid moiety and diol-containing PVA by using benzaldehyde-functionalized PEG as control polymer. Gel strength (represented by plateau values), shape stability (represented by relaxation time), and visual appearance of hydrogels formed with these novel linkers and PVA can be tuned by proper adjustment of molecular architecture, molecular weight (MW) and concentration of both the PEG-linker and the PVA, and the method of preparation. Due to the relatively high solubility of the linkers in water, transparent hydrogels ranging from weak and sticky to strong and brittle can be obtained, widening the prospect of potential commercial applications. By keeping the amount of the crosslink (concentration of the boronic acid moiety) constant, the storage modulus based on rheological measurement was found to increase with the increase in number of arm, suggesting a positive cooperativity in the binding or complexation mechanism. On the other hand, storage modulus decreases as the arm length of the linker was increased, with phase-separation playing critical role in influencing the gel strength of hydrogels with relatively higher concentration and/or MW of PEG. At high PEG content, phase-separation tends to occur and these ‘turbid and cloudy’ hydrogels are found to be weak with low storage moduli. Further, preliminary swelling, degradation, and drug release study was done using diol-containing ARS (1,2-dihydroxy-9-10-anthraquinone sulfonic acid) as the model drug. The rate of degradation of the hydrogels prepared with this novel linker system and PVA was proportional to the gel strength; with the strongest gel being still not completely degraded (~70% swelling ratio) after two weeks of incubation in PBS buffer pH 7.4 at 37°C. The entrapped ARS molecules were found to be released in their complexed form with boronic acid moieties of the linker, hand in hand with hydrogel degradation. With a homogeneous ARS-containing hydrogel, zero order controlled release of the entrapped ARS molecules can be achieved.